Peran Pendidikan Agama Islam dalam Membangun Moralitas Siswa di Era Digital (Studi di SMP IT Mutiara Aulia Sei Mencirim) - Sipahutar, Nurhasanah; Wandini, Rora Rizki; Suheri , Muhammad (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to examine the role of Islamic religious education in building student morality in the digital era, focusing on a case study at SMP IT Mutiara Aulia Sei Mencirim. The digital age has a significant impact on student behavior, especially in the context of morality. This study aims to determine the role of Islamic religious education in building student morality in the digital era. The research method used is qualitative with a case study approach. The subjects of the study were selected by purposive sampling. Data was collected through observation, interviews, and document studies at SMP IT Mutiara Aulia Sei Mencirim. Data analysis is carried out with a qualitative data analysis approach, namely data reduction, data presentation, and conclusions. The results of data analysis show that Islamic religious education at SMP IT Mutiara Aulia Sei Mencirim has an important role in guiding students to face this challenge. Islamic teachers act as facilitators of moral learning who integrate Islamic religious values in students' daily lives. The research formulated several strategies that can be applied by SMP IT Mutiara Aulia Sei Mencirim to strengthen the role of Islamic religious education in the digital era, including responsive curriculum development, Islamic teacher training, and integration of religious values in school activities.